Digital transformation in rural settings: Unlocking opportunities for sustainable economic growth and community empowerment - Asep Kosasih; Eman Sulaiman (Journal of Sustainable Tourism and Entrepreneurship, 2024)
Purpose: This study explores the potential of digital transformation in rural settings and its role in unlocking opportunities for sustainable economic growth and community empowerment. Method: This study employed a mixed-methods approach that included both qualitative and quantitative research methods. In-depth interviews were conducted with key stakeholders from rural communities, government agencies, and technology experts to gain insights into the current state of digital transformation in rural settings. A survey was also administered to assess their digital literacy levels and attitudes towards digital technologies. Results: The study revealed that the adoption of digital technologies can enhance access to information, improve connectivity, and create new economic opportunities for rural communities. It also demonstrates that digital transformation initiatives can empower community members by providing them with the skills and resources necessary to participate in the digital economy. Furthermore, this study identifies several key success factors for implementing digital transformation in rural areas, including infrastructure development, capacity building, and collaboration between stakeholders. Limitations: This study acknowledges certain limitations, such as the focus on a specific geographic area and potential for response bias in the survey. Further research is needed to explore the generalizability of the findings and to examine the long-term impacts of digital transformation in rural settings. Contributions: This study contributes to understanding the potential benefits of digital transformation in rural settings for sustainable economic growth and community empowerment. These findings provide insights for policymakers, community leaders, and technology providers in designing and implementing effective strategies for digital inclusion and rural development.